2002
DOI: 10.1111/j.1748-0361.2002.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Not Raising a “Bubble Kid”: Farm Parents'Attitudes and Practices Regarding the Employment, Training and Supervision of Their Children

Abstract: This article explores farm parents' attitudes and practices regarding the employment, training and supervision of their children among a sample of 24 farm couples from southeastern Washington state. The goal was to gain a greater understanding of parental attitudes and practices in order to devise appropriate and meaningful efforts to improve the safety of children and adolescents involved in farm work. Demographic data regarding the farm families and their farm safety practices were collected through a short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…As in earlier studies, 12 , 18 the parents and children whom we interviewed believe children should work on farms and that parents know best about child maturity and safety. Our results are similar to other findings that suggest that children participate in the full range of production tasks that parents felt were age appropriate.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…As in earlier studies, 12 , 18 the parents and children whom we interviewed believe children should work on farms and that parents know best about child maturity and safety. Our results are similar to other findings that suggest that children participate in the full range of production tasks that parents felt were age appropriate.…”
Section: Discussionmentioning
confidence: 73%
“…14 , 26 , 27 Without relevant data describing the work of children working on LAMP farms, the development of these safety programs cannot progress. Neufeld and colleagues 18 concluded that because parents’ practices regarding child farm work reflect their beliefs and values regarding child-rearing, recommended safety guidelines, such as delaying farm work and not riding on farm machinery, will be difficult to implement. It is important that the beliefs and values of parents, as well as their perceptions of their children working on their farms, be documented in further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12−16 Studies have also considered farm parents' beliefs about the safety of their children working on the farm. 17,18 However, little primary research has addressed the safety and health of youth employed in agriculture. Westaby and Lee 19 completed a national survey of Future Farmers of America (FAA) members and found that dangerous risk taking was the strongest predictor of injury.…”
Section: Introductionmentioning
confidence: 99%